2019
DOI: 10.1080/2090598x.2019.1595485
|View full text |Cite
|
Sign up to set email alerts
|

Management of ‘forgotten’ encrusted JJ stents using extracorporeal shockwave lithotripsy: A single-centre experience

Abstract: Objective: To evaluate the role of extracorporeal shockwave lithotripsy (ESWL) for the management of 'forgotten' encrusted stents. Patients and Method: This is a retrospective study of 133 patients with forgotten JJ stents, treated between January 2015 and January 2018. Encrustation was mainly found in the renal coil of the stent with distal concomitant encrustation in the vesical and/or ureteric segment. After laboratory and radiological assessment, treatment started with ESWL for the renal encrustation befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Ulker et al ( 17) treated 17 patients with a 58.9% stone-free rate in a single procedure, however, they were evaluated with KUB. Given that treat- ment is generally difficult, with potential hazardous complications (18,20,21), we believe that these cases should be referred to high volume endourological centers with experienced staff. Compared to other grading systems for encrusted stents, the FECal classification system developed by Acosta-Miranda et al incorporate both stone location and size (3).…”
Section: Discussionmentioning
confidence: 99%
“…Ulker et al ( 17) treated 17 patients with a 58.9% stone-free rate in a single procedure, however, they were evaluated with KUB. Given that treat- ment is generally difficult, with potential hazardous complications (18,20,21), we believe that these cases should be referred to high volume endourological centers with experienced staff. Compared to other grading systems for encrusted stents, the FECal classification system developed by Acosta-Miranda et al incorporate both stone location and size (3).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sessions may be required. Previous studies have indicated a relatively high success [7-9]. Existing literature also shows that endourological treatment is feasible even in complex cases [10].…”
Section: Background and Annotationsmentioning
confidence: 99%
“…The management of forgotten JJ stent constitutes a dilemma to the urologist and sometimes may be difficult, complicated, risky and expensive. Although open surgery has been reported as a treatment modality, other minimally invasive procedures are followed; of these techniques, extracorporeal shockwave lithotripsy (ESWL), or internal lithotripsy with percutaneous nephrolithotomy (PCNL), cystolithotripsy (CLT), ureteroscopic lithotripsy (URL) have all been used either alone or in combination to tackle this problem [ 5 ].…”
Section: Introductionmentioning
confidence: 99%